Activities of English agents in central asia in the first half of the XIX century in the context of Russian-English rivalry (Journal of history, 2022)
The article is devoted to the activities of British intelligence officers, diplomats, military, travelers and scientists sent to the territory of Central Asia in the first half of the XIX century. England’s policy in the region was conditioned by the protection of its colonies in Asia. The actions carried out by England and Russia in Central Asia throughout the XIX century until the beginning of the First World War in history are called as “Great Game”, which implies Anglo-Russian rivalry in the region. During the period under review, this rivalry was mainly reflected by mutual threats and the dispatch of various intelligence missions. They were led by military or scientists who had certain qualities like knowledge of local languages or endurance. The information and reports that were transmitted by these persons in many ways even determined the course of the empire’s policy. Therefore, the study of their activities is important in the history of Central Asia. The purpose of this reserch is to study the activities of English agents, their goals, objectives and outcomes in the first half of the XIX century and the impact of their activities on the course of Russian-English rivalry in the region. To achieve this goal, the following tasks are: to identify the main figures of British intelligence in Central Asia in first half of XIX century, to determine the influence of the activities of English agents in Russian-English relations. Key words: Central Asia, England, Big Game, scout, missions, diplomat.